Penerapan Media Audio Visual Dalam Meningkatkan Motivasi Belajar Materi Pendidikan Pancasila Kelas 4 SDN 04 Krajankulon - Hikmatun Mutingah; Ika Rizqi Ariyani; Nur Indah Wahyuni; Frida Atma Nuraeni (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to explore in more detail the use of audio-visual learning media in increasing students' learning motivation in Pancasila Education subjects in grade 4 SD Negeri 04 Krajankulon. The method used in this research is a qualitative method with a descriptive approach so that researchers know the description or situation of classroom conditions as well as students' understanding and enthusiasm in learning Pancasila Education clearly in grade 4 SD Negeri 04 Krajankulon. The object of this research is 4th grade students of SD Negeri 04 Krajankulon, totaling 24 students. The instruments used are interviews and tests which are carried out orally and in writing after applying audio-visual media in learning. From the results of the study, it was obtained that grade 4 students at SD Negeri 04 Krajankulon looked enthusiastic about learning and were easy to condition. In addition, the use of audio-visual learning media also requires a lot of time for preparation and preparation. Thus, teachers can sort and choose any material that is necessary to use this learning media. Overall, this audio-visual learning media is good to use in learning Pancasila Education and is highly recommended to be tried in other subjects.